ENHANCING SECONDARY STUDENTS’ MATHEMATICAL CREATIVE THINKING THROUGH STEM PROJECT-BASED LEARNING - Ferdiansyah, Fiko; Sri Hastuti Noer; Widyastuti, Widyastuti (KALAMATIKA Jurnal Pendidikan Matematika, 2025)
Studies have highlighted the persistently low levels of mathematical creative thinking skills among students, emphasizing the need for innovative learning interventions. The STEM-PjBL model, which integrates science, technology, engineering, and mathematics through project-based learning, offers a structured framework to enhance these skills by fostering innovative problem-solving. This study investigates the implementation of the STEM-PjBL model to improve students' mathematical creative thinking skills. A quantitative quasi-experimental approach with pre- and post-tests control group design was used, involving two purposively selected ninth-grade classes from a population of 298 students. Analysis using the Mann-Whitney U test showed a statistically significant improvement in mathematical creative thinking skills following the STEM-PjBL intervention (p < 0.05), with a normalized gain (g = 0.43), indicating that the results for the experimental group were higher than those of the control group. These findings suggest that the STEM-PjBL model is an effective strategy for improving creative thinking in mathematics education.